Isolation and identification of phosphate solubilizing bacteria and evaluate its effect on of Mung bean (Vigna radita [L.] R.Wilczek) growth - Ramzi, Yusur; Alsalim, Hutaf A. A. (Iraqi Journal of Science, 2019)
Sixteen soil samples were collected from wheat, barley and yellow corn rhizosphere in Abu-Ghraib, Aqraqof, Latifieh,Tarmiah, Jadriya and of Agriculture in Baghdad university/ Baghdad city. The results found nine phosphate solubilizing bacteria (PSB) isolates (Y1, Y2, Y3, Y4, Y5, Y6, Y7, Y8, Y9), formed clear zones on National Botanical Research Institute's (NBRIP) agar. The solubility index (SI) of PSB isolates ranged from 2.00 to 3.66. Y4 have the highest SI (3.66) followed by Y3 and Y6 (3.33). Phosphate solubilization abilities varying from (20.10-39.00 Î¼g.ml-1), Y4 was the highest (39.00 Î¼g.ml-1) followed by Y3 (37.00Î¼g.ml-1). The results of hydrolytic enzymes production showed that almost all nine isolates are able to produce protease and pectinase, while Y1 and Y2 showed negative results in cellulase production. Maximum ability for hydrogen cyanide (HCN) and indole acetic acid (IAA) production were showed byY3 and Y4 isolates. The isolate Y4 was found to be the most efficient isolate, so it was selected identified as Bacillus cereus using biochemical tests confirmed by VITEC 2 compact system. The results of High performance liquid chromatography (HPLC) revealed that Bacillus cereus produce oxalic acid (2.996), citric acid (9.117) and malic acid (3.734). Bacillus cereus (Y4) enhanced the growth of mung bean plants. A significant increase in branches number (12.33), plant length (83.0cm), fresh weight (27.25 g) and dry weight (1.427g) were obtained compared with control treatments. The main objective of this study is to isolate PSB and evaluate their roles in plant growth promotion. The results showed the high phosphate solubilization efficiency of PSB isolates and the identified isolates was found to be good enough for plant growth promoting.